2022
DOI: 10.3389/fpsyg.2022.844234
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of College Entrepreneurship Education System on the Cultivation of Applied Innovative Talents

Abstract: With China’s socioeconomic development, especially in the educational sector, foreign advanced education experience might not be omnipotent for the innovation and entrepreneurship education (IEE) in Chinese colleges. In response to such a difficult context, firstly, this study was conducted to analyze the applied innovative talent cultivation status quo in Chinese colleges under innovation and entrepreneurship. Then, the authors dug into the current situation and the development of IEE-related courses in Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Yanli Ma is incorporating artificial neural networks into the cultivation process of developing film creation talent [ 27 ]. Additionally, for the past few years, a significant body of literature has addressed the cultivation of innovative talent, emphasizing the need for colleges and universities to revise their understanding and optimize their faculty structure [ 28 , 29 ], the reform of educational concepts, models, and policies [ 30 ], and the reform of curricula [ 31 , 32 ]. Zhang, H et al suggested dismantling institutional obstacles, fostering collaboration and talent exchange, and implementing a talent-sharing mechanism [ 33 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yanli Ma is incorporating artificial neural networks into the cultivation process of developing film creation talent [ 27 ]. Additionally, for the past few years, a significant body of literature has addressed the cultivation of innovative talent, emphasizing the need for colleges and universities to revise their understanding and optimize their faculty structure [ 28 , 29 ], the reform of educational concepts, models, and policies [ 30 ], and the reform of curricula [ 31 , 32 ]. Zhang, H et al suggested dismantling institutional obstacles, fostering collaboration and talent exchange, and implementing a talent-sharing mechanism [ 33 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an important part of China's vocational education, the main task of higher vocational education is to cultivate a large number of applied and skilled talents for society [2] . However, there are some problems in the current higher vocational education in cultivating students' vocational qualities, such as unreasonable curriculum setting, single teaching methods, and imperfect evaluation system [3] . These problems affect the improvement of students' vocational quality to a certain extent and affect the service ability of higher vocational education for social and economic development [4] .…”
Section: Research Background and Significancementioning
confidence: 99%
“…Under the background of the current global epidemic of new coronavirus, many countries and regions are facing the risk of economic recession, and the employment problem is becoming increasingly serious [3]. erefore, promoting IE in the whole society is an important method to solve the employment problem and promote the development of industrial upgrading [4,5]. IE is a kind of entrepreneurial activity based on innovation [6].…”
Section: Introductionmentioning
confidence: 99%